2014
DOI: 10.1111/jam.12589
|View full text |Cite
|
Sign up to set email alerts
|

Anti-quorum sensing activity of AgCl-TiO2 nanoparticles with potential use as active food packaging material

Abstract: Food spoilage is a major socio-economic problem, and the potential role of QS in food spoilage and food safety has been indicated. Anti-QS materials such as ATNPs are proposed as efficient models for controlling food spoilage. ATNPs incorporated in food packaging materials could play an important role in food preservation and ensure safety of food by prolonging their shelf life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…The findings of colorimetric assay revealed significant reduction in violacein at all tested concentrations (50–400 μg/ml) of NS-ZnNPs. Our findings on QS inhibition in Chromobacetrium violaceum biosensor strain are well supported by those reported with silver nanowires (80% inhibition), mycofabricated silver nanoparticles (100% violacein inhibition) and AgCl-TiO 2 nanoparticles44647.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of colorimetric assay revealed significant reduction in violacein at all tested concentrations (50–400 μg/ml) of NS-ZnNPs. Our findings on QS inhibition in Chromobacetrium violaceum biosensor strain are well supported by those reported with silver nanowires (80% inhibition), mycofabricated silver nanoparticles (100% violacein inhibition) and AgCl-TiO 2 nanoparticles44647.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the importance of QS in food microbial ecology, development of novel food preservatives, packing materials that can specifically block QS and prevent losses due to spoilage of food is the need of the hour23. Quorum sensing or cell-to-cell communication between bacteria commonly associated with contamination of food takes place by the production of signaling molecules called autoinducers and this bacterial cross talk can be intra as well inter species specific4. Quorum sensing is known to regulate several proteolytic, lipolytic, chitinolytic, and pectinolytic activities associated with the deterioration of foods.…”
mentioning
confidence: 99%
“…The antibacterial properties of AgCl-TiO 2 nanoparticles against Chromobacterium violaceum were purposed for a potential use in active food packaging (Naik and Kowshik, 2014). In the case of fungi species, most of publications refer to tests where antimicrobial activities of AgNPs were examined in relation to clinical isolates of Candida albicans, Trichophyton rubrum, Trichophyton mentagrophytes, and Aspergillus niger (Panáček et al, 2009;Narayanan and Park, 2014;Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ZnO nanoparticles have been tested against six clinical bacterial strains of Pseudomonas aeruginosa and found that they decreased the virulence production and biofilm formation for most of the strains [59]. Several mechanisms have been proposed for the inhibition of bacterial QS activity, Naik et al evaluated AgCl-TiO2 nanoparticles with Chromobacterium violaceum for their anti-QS activity, their studies confirmed that the inhibition of violacein production was due to AHL inhibition while not repressing bacterial growth [32]. Mohanty et al quantified the influence of silver nanoparticles and single-wall carbon nanotubes on the reduction of the AHL synthesis and revealed that the effects of nanomaterials on QS signaling are highly dependent on bacterial species [30].…”
Section: Effect Of Nanocapsules On the Bacterial Quorum Sensing Activmentioning
confidence: 99%
“…In particular, in the recent years, an increasing number of studies have focused on exploring the impacts of nanomaterials on bacterial QS signaling. [30][31][32][33] These have included the study of nanomaterials loaded either with QS inhibitors [34], or with AIs, as well as polymeric materials obtained by molecular imprinting with high recognition capacity to sequester AHLs, and thus inhibit QS responses [35,36].…”
Section: Introductionmentioning
confidence: 99%